2019
DOI: 10.1002/celc.201900371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li+ and Mg2+ on the Electrochemical Decomposition of the Ionic Liquid 1‐Butyl‐1‐ methylpyrrolidinium bis(trifluoromethanesulfonyl)imide and Related Electrolytes

Abstract: We investigated the decomposition of 1‐butyl‐1‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (BMP‐TFSI) based electrolytes on Au and glassy carbon (GC) in the absence and presence of Li(TFSI) and Mg(TFSI)2. Detecting the volatile reaction products via differential electrochemical mass spectrometry (DEMS) measurements allowed us to gain insight into the decomposition mechanisms. In neat ionic liquid (IL) and on Au electrodes both ions are decomposed at reductive potentials. The TFSI− anion mainly decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
(89 reference statements)
2
23
1
Order By: Relevance
“…It is not clear if, especially on the graphite powder electrode, the latter process is also accompanied by Li + or [BMP] + intercalation and whether it results in the formation of a surface layer that passivates against further insertion processes. In recent differential electrochemical mass spectrometry (DEMS) studies, we found indirect evidence for the formation of adsorbed decomposition products in Li + ‐containing [BMP][TFSI] . This was concluded from the lack of volatile decomposition products during the reduction in Li + ‐containing electrolyte, whereas [BMP] + and [TFSI] − fragments were found in neat and Mg 2+ ‐containing IL …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is not clear if, especially on the graphite powder electrode, the latter process is also accompanied by Li + or [BMP] + intercalation and whether it results in the formation of a surface layer that passivates against further insertion processes. In recent differential electrochemical mass spectrometry (DEMS) studies, we found indirect evidence for the formation of adsorbed decomposition products in Li + ‐containing [BMP][TFSI] . This was concluded from the lack of volatile decomposition products during the reduction in Li + ‐containing electrolyte, whereas [BMP] + and [TFSI] − fragments were found in neat and Mg 2+ ‐containing IL …”
Section: Resultsmentioning
confidence: 98%
“…In recent differential electrochemical mass spectrometry (DEMS) studies, we found indirect evidence for the formation of adsorbed decomposition products in Li + ‐containing [BMP][TFSI] . This was concluded from the lack of volatile decomposition products during the reduction in Li + ‐containing electrolyte, whereas [BMP] + and [TFSI] − fragments were found in neat and Mg 2+ ‐containing IL …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, the atomic concentration of all elements is summarized in Figure f, which further highlights the reduction in oxygen‐containing species at the Li surface and an increase in carbon species upon addition of the IL. This points to a mechanism in which the decomposition of Py 1,4 TFSI leads to the formation of a polymeric SEI, rather than inorganic species, with the added benefit of a reduction of sulfur deposition …”
Section: Resultsmentioning
confidence: 99%
“…This points to amechanism in which the decompositiono fP y 1,4 TFSI leads to the formation of ap olymeric SEI, rather than inorganic species, with the added benefit of ar eductiono fsulfur deposition. [41] To further confirmt he effect of Py 1,4 TFSI as an additive to the ether-based electrolyte solution, the IL50 mixture, that is, the best-performing in terms of cycling stability and coulombic efficiency,w as compared with as tandard DOL/DME1 m LiTFSI electrolyte using LiNO 3 (0.4 m)a sa na dditive in Li/S cells. [16] The voltage profiles of the Li/S cellsw ith the two electrolytes for different cycles are reported in Figure 5a.T he cell containing the IL additive (left panel)h ad the highest discharge capacity during the first cycle, 20 %h igher than the cell containing the LiNO 3 additive.…”
Section: Solid Electrolyte Interphase At the LI Surfacementioning
confidence: 99%